On The Spot (Realtime) Accident Information & Insurance Dispute Resolution - et. al., M.Rajkumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There should be a system/portal forgathering of on the spot information during roadaccidents. This information should include photos ofthe site, interviews with eyewitnesses, informationon injuries and fatalities, reason for accident, speed ,road condition on relative basis, etc. All this data cango into a central database. This responsibility forcollecting the data could be given either to police, transport authority, ambulance or even ordinarycitizens who volunteer for the same. In the samesystem, there should also be a provision to submit/exchange insurance numbers/ details in order tosettle the dispute if any arising out of the accident.